Advances in Medical Toxicology: Innovative Approaches for Poisoning and Overdose Management - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2025)
Medical toxicology has rapidly evolved with innovative approaches to managing poisoning and overdose, integrating advances in pharmacology, biotechnology, and precision medicine. Poisoning from chemicals, drugs, and environmental agents remains a major public health challenge globally. Novel diagnostic tools, such as highthroughput mass spectrometry and point-of-care toxicological assays, have significantly improved the speed and accuracy of identifying toxic agents. Precision medicine has introduced individualized detoxification protocols tailored to genetic profiles and specific metabolic pathways, enhancing the efficacy and safety of treatments. Recent developments in extracorporeal treatments, including hemodialysis and hemoperfusion, allow for more effective removal of toxins, particularly for substances that are poorly eliminated by the body. Artificial intelligence and machine learning algorithms are being integrated into clinical toxicology to predict outcomes, optimize antidote dosing, and improve clinical decision-making. Mobile health platforms and telemedicine have expanded access to toxicology expertise, particularly in remote or underserved areas, facilitating real-time consultations in emergency scenarios. The adoption of these cutting-edge technologies is reshaping the landscape of poisoning and overdose management, moving toward more targeted, efficient, and patient-specific interventions. This review highlights key innovations in medical toxicology and emphasizes the need for continued research and interdisciplinary collaboration to improve outcomes for patients affected by toxic exposures.